العلاقات الصينية الجزائرية في ظل مبادرة الحزام والطريق: المكاسب والتحديات. - بوالروايح عبد القادر; زياني زيدان (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
يهدف المقال لتسليط الضوء على موضوع انضمام الجزائر إلى مبادرة الحزام والطريق للقرن 21 في سياق التطور الذي باتت تشهده العلاقات الصينية الجزائرية في ظل التحولات العالمية الراهنة. وتتمحور إشكالية الدراسة حول مدى امبريقية المكاسب المنتظرة التي تراهن الجزائر على تحقيقها من خلال المبادرة، وقد توصلت الدراسة إلى نتيجة مفادها أن انضمام الجزائر للمبادرة من شأنه تعزيز المكاسب الاقتصادية وتقوية البنى التحتية رغم ما تفرزه التحولات العالمية الراهنة من تحديات تتصل بعدم استقرار النظام العالمي. The article aims to shed light on the issue of Algeria’s accession to the Belt and Road Initiative for the 21st century in the context of the development that Sino-Algerian relations are witnessing in light of the current global transformations. The problematic of the study revolves around the extent of the imperialism of the expected gains that Algeria is betting on achieving through the initiative. The study concluded that Algeria’s accession to the initiative would enhance economic gains and strengthen infrastructure, despite the challenges posed by the current global transformations related to the instability of the global system.